Representation of Multicultural Values in Indonesian and English Textbooks for Junior High School - Mursia Ekawati; Herpindo Herpindo; Jendriadi Jendriadi; Irsyadi Shalima; Ryan Prasetya; Wastiana Wastiana (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This research is motivated by the need to understand how multicultural values ​​are represented in language textbooks used in junior high schools (SMP) in Indonesia, considering that language education plays a crucial role in shaping students' character and social awareness. This study aims to identify and analyze the representation of multicultural values ​​reflected in the text and visuals of Indonesian and English textbooks published by the Ministry of Education and Culture. This study uses a descriptive qualitative approach with Fairclough's Critical Discourse Analysis (CDA) method, which views language as a social practice. Research data were obtained through documentation, learning observations, and teacher interviews to gain a contextual understanding of students' interpretations of multicultural values. The results show that both textbooks have presented ethnic, cultural, and religious diversity, but the representation is still symbolic and not entirely critical. Multicultural values ​​are more dominant in the visual aspect than in the text, while the integration between the two is still weak. These findings confirm that language textbooks are not merely linguistic learning tools, but also ideological means that shape students' social awareness. Therefore, this study recommends developing textbooks and pedagogical strategies that are more reflective, contextual, and oriented towards multicultural character education.